Involving the other half: male perception of BRAC's health program - Shahaduzzaman; Chowdhury, AMR; Karim, Fazlul (BRAC Research and Evaluation Division (RED), 2019)
In July 1991, BRAC integrated its diverse health activities into the newly established Women Health and Development Programme (WHDP). But as men play a key role in making decisions in deferent spheres of women's life, health programme managers increasingly recognize the importance of male involvement in women focused health program. This study was therefore done with the objectives, to determine the knowledge, attitude and felt need of the male population of the community regarding BRAC's Women's Health and Development Program. The principal investigator stayed for nearly a month (Jan1996) with a family in a typical village of a WHDP working area to gather information. Informal conversation , key informant interview and observation of health care service delivery was done . The study reveals that , men have a gep.eralized feeling of being neglected by the BRAC's health program. Men have knowledge only about the curative components of the programme though more programmatic input was given to the preventive components. Contradictory attitude was revealed among men regarding BRAC's programme. This was also found that there is lack of regular male contact by the field workers. However. a strong felt need \vas expressed by most men regarding health information and services. In order to ensure male involvement in the program. it was recommended to organize orientation session for field workers on male involvement, to strengthen male torums, to specify male audience, to open male only clinic and to recruit male community health workers.